2017
DOI: 10.3389/fmicb.2017.00575
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Rare PB2-D701N Mutation from a Patient with Severe Influenza: Contribution of the PB2-D701N Mutation to the Pathogenicity of Human Influenza

Abstract: Several amino acid changes have been previously implicated in adaptation of avian influenza viruses to human hosts, among them the D701N change in the PB2 polymerase subunit that also is the main determinant of avian virus pathogenesis in animal models. However, previous studies using recombinant viruses did not provide conclusive information of the contribution of this PB2 residue to pathogenicity in human influenza virus strains. We identified this mutation in an A(H1N1)pdm09-like human influenza virus isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Influenza can cause a mild respiratory illness but can also lead to respiratory failure and death [2,3]. Virulence factors (of different virus strains) contribute significantly to this variability in infection severity [4,5]. However, it is increasingly being recognized that host factors also play an important role in contributing to infection severity [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Influenza can cause a mild respiratory illness but can also lead to respiratory failure and death [2,3]. Virulence factors (of different virus strains) contribute significantly to this variability in infection severity [4,5]. However, it is increasingly being recognized that host factors also play an important role in contributing to infection severity [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid diffusion of NGS into clinical laboratories for detecting respiratory viruses will be based on whether the challenges relating to NGS can be addressed. 39,42,46,48,49,78 Notably, the cost of NGS has been reduced over time, which will attract more laboratories to bring this technique into their research and make efforts in optimising NGS protocols.…”
Section: Discussionmentioning
confidence: 99%
“…14 Nieto et al observed the D701N mutation of polymerase basic protein 2 (PB2) segment of the H1N1pdm09 virus in one patient with severe influenza. 46 The study provided evidence on the association between the PB2-D701N mutation and viral pathogenicity in humans and suggested that this mutation may result in more severe clinical outcomes of human infections.…”
Section: Influenzaviruses Type a And Bmentioning
confidence: 96%
See 2 more Smart Citations